Welcome to Westonci.ca, the ultimate question and answer platform. Get expert answers to your questions quickly and accurately. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
Certainly! Let's solve the given quadratic equation step by step.
### Given:
The quadratic equation is [tex]\(2x^2 + kx - 2 = 0\)[/tex] and one of its roots is [tex]\( x_1 = 2 \)[/tex].
### Part (a): Determine the value of [tex]\( k \)[/tex].
#### Step 1: Use Vieta’s formulas which relate the coefficients of a polynomial to sums and products of its roots.
For a quadratic equation of the form [tex]\( ax^2 + bx + c = 0 \)[/tex], Vieta's Formulas tell us:
1. The sum of the roots [tex]\((x_1 + x_2)\)[/tex] is equal to [tex]\( -\frac{b}{a} \)[/tex].
2. The product of the roots [tex]\((x_1 \cdot x_2)\)[/tex] is equal to [tex]\(\frac{c}{a}\)[/tex].
Here, [tex]\( a = 2 \)[/tex], [tex]\( b = k \)[/tex], and [tex]\( c = -2 \)[/tex].
#### Step 2: Apply Vieta’s formulas to find the sum of the roots.
Since one root is [tex]\( x_1 = 2 \)[/tex], let the other root be [tex]\( x_2 \)[/tex].
The sum of the roots is:
[tex]\[ x_1 + x_2 = -\frac{k}{2} \][/tex]
Substituting [tex]\( x_1 = 2 \)[/tex]:
[tex]\[ 2 + x_2 = -\frac{k}{2} \][/tex]
#### Step 3: Apply Vieta’s formulas to find the product of the roots.
The product of the roots is:
[tex]\[ x_1 \cdot x_2 = \frac{-2}{2} \][/tex]
[tex]\[ 2 \cdot x_2 = -1 \][/tex]
Solving for [tex]\( x_2 \)[/tex]:
[tex]\[ x_2 = -\frac{1}{2} \][/tex]
#### Step 4: Substitute [tex]\( x_2 \)[/tex] back into the sum of the roots equation to solve for [tex]\( k \)[/tex].
[tex]\[ 2 + \left(-\frac{1}{2}\right) = -\frac{k}{2} \][/tex]
[tex]\[ 2 - \frac{1}{2} = -\frac{k}{2} \][/tex]
[tex]\[ \frac{4}{2} - \frac{1}{2} = -\frac{k}{2} \][/tex]
[tex]\[ \frac{3}{2} = -\frac{k}{2} \][/tex]
Multiplying both sides by 2 to solve for [tex]\( k \)[/tex]:
[tex]\[ 3 = -k \][/tex]
Hence,
[tex]\[ k = -3 \][/tex]
### Part (b): What is the other root?
We have already determined the other root while solving for [tex]\( k \)[/tex].
From the product of the roots:
[tex]\[ x_1 \cdot x_2 = \frac{-2}{2} \][/tex]
[tex]\[ 2 \cdot x_2 = -1 \][/tex]
[tex]\[ x_2 = -\frac{1}{2} \][/tex]
### Final Answer
(a) The value of [tex]\( k \)[/tex] is [tex]\(-3\)[/tex].
(b) The other root is [tex]\(-\frac{1}{2}\)[/tex].
Summary:
1. [tex]\( k = -3 \)[/tex]
2. The other root [tex]\( x_2 = -\frac{1}{2} \)[/tex]
### Given:
The quadratic equation is [tex]\(2x^2 + kx - 2 = 0\)[/tex] and one of its roots is [tex]\( x_1 = 2 \)[/tex].
### Part (a): Determine the value of [tex]\( k \)[/tex].
#### Step 1: Use Vieta’s formulas which relate the coefficients of a polynomial to sums and products of its roots.
For a quadratic equation of the form [tex]\( ax^2 + bx + c = 0 \)[/tex], Vieta's Formulas tell us:
1. The sum of the roots [tex]\((x_1 + x_2)\)[/tex] is equal to [tex]\( -\frac{b}{a} \)[/tex].
2. The product of the roots [tex]\((x_1 \cdot x_2)\)[/tex] is equal to [tex]\(\frac{c}{a}\)[/tex].
Here, [tex]\( a = 2 \)[/tex], [tex]\( b = k \)[/tex], and [tex]\( c = -2 \)[/tex].
#### Step 2: Apply Vieta’s formulas to find the sum of the roots.
Since one root is [tex]\( x_1 = 2 \)[/tex], let the other root be [tex]\( x_2 \)[/tex].
The sum of the roots is:
[tex]\[ x_1 + x_2 = -\frac{k}{2} \][/tex]
Substituting [tex]\( x_1 = 2 \)[/tex]:
[tex]\[ 2 + x_2 = -\frac{k}{2} \][/tex]
#### Step 3: Apply Vieta’s formulas to find the product of the roots.
The product of the roots is:
[tex]\[ x_1 \cdot x_2 = \frac{-2}{2} \][/tex]
[tex]\[ 2 \cdot x_2 = -1 \][/tex]
Solving for [tex]\( x_2 \)[/tex]:
[tex]\[ x_2 = -\frac{1}{2} \][/tex]
#### Step 4: Substitute [tex]\( x_2 \)[/tex] back into the sum of the roots equation to solve for [tex]\( k \)[/tex].
[tex]\[ 2 + \left(-\frac{1}{2}\right) = -\frac{k}{2} \][/tex]
[tex]\[ 2 - \frac{1}{2} = -\frac{k}{2} \][/tex]
[tex]\[ \frac{4}{2} - \frac{1}{2} = -\frac{k}{2} \][/tex]
[tex]\[ \frac{3}{2} = -\frac{k}{2} \][/tex]
Multiplying both sides by 2 to solve for [tex]\( k \)[/tex]:
[tex]\[ 3 = -k \][/tex]
Hence,
[tex]\[ k = -3 \][/tex]
### Part (b): What is the other root?
We have already determined the other root while solving for [tex]\( k \)[/tex].
From the product of the roots:
[tex]\[ x_1 \cdot x_2 = \frac{-2}{2} \][/tex]
[tex]\[ 2 \cdot x_2 = -1 \][/tex]
[tex]\[ x_2 = -\frac{1}{2} \][/tex]
### Final Answer
(a) The value of [tex]\( k \)[/tex] is [tex]\(-3\)[/tex].
(b) The other root is [tex]\(-\frac{1}{2}\)[/tex].
Summary:
1. [tex]\( k = -3 \)[/tex]
2. The other root [tex]\( x_2 = -\frac{1}{2} \)[/tex]
Thank you for trusting us with your questions. We're here to help you find accurate answers quickly and efficiently. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.